Pengaruh Pola Asuh Orangtua Terhadap Tingkat Kedisiplinan Siswa - Laksono, Rizky Agung (Jurnal Gemaedu, 2018)
The purpose of this research is to know the influence of parenting pattern on student discipline level. The research method used is Exposfakto Survey method. The population in this study as many as 98 students. The technique of sampling is done by simple random sampling (Simple Random Sampling) with the calculation of Slovin formula so that the sample number of 79 students is obtained. Measurement and retrieval data influence parenting to student discipline level using a questionnaire instrument (questionnaire) in the form of a statement with five answer choices. Previously this instrument has been tested the level of validity and reliability. Test data analysis requires that is used normality test using Liliefors test where the result obtained is three group of normal distribution data Then tested homogeneity using Bartlett test, where result obtained is three data group have the same variance or homogeneous. Furthermore, in testing the hypothesis of data using the test Analysis of Variance (ANAVA) one path where at signification level α = 5% obtained score F_ (table) = 3.13; while the price F_ (count) = 0.68. Based on these results it turns out that F_ (count) <F_ (table) is 0.68 <3.13, thus H_0 is accepted so it can be concluded that there is an insignificant influence parenting to student discipline.